See under: Shoah : imagining the Holocaust with David Grossman - Kesel, Marc De; Siertsema, Bettine; Szurmiak, Katarzyna (Brill reference library of Judaism, 2014)
"Did the first generation Holocaust writers not warn us against the risks of imagination? Does it not create an illusion that the unimaginable can be imagined, the unrepresentable represented? Clearly this warning has not been taken up by David Grossman. Fully embracing imagination's power, his novel See Under: Love offers a profound reflection on how the twenty-first century can assume the heritage of the Shoah and remember the 'unmemorable' in a proper way. The essays in this volume reflect on this one novel, though each from its own angle. Focusing on one single novel shows the surplus value of a multispectral reflection on one central problem, in this case the allegedly inconceivable and unspeakable nature of the Shoah"--